2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Adrenergic Antagonists on In-Hospital Mortality after Ischemic Stroke

Abstract: Background Ischemic stroke accounts for 85–90% of all strokes and currently has very limited therapeutic options. Recent studies of β-adrenergic antagonists suggest they may have neuroprotective effects that lead to improved functional outcomes in rodent models of ischemic stroke, however there is limited data in patients. We aimed to determine whether there was an improvement in mortality rates among patients who were taking β-blockers during the acute phase of their ischemic stroke. Methods A retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
6
0
5
Order By: Relevance
“…In conclusion, we could not provide evidence for a protective effect of beta-blockers on post stroke infections and mortality. Data in humans remain inconclusive with studies showing protective effects on pneumonia rates [ 13 , 14 ] and mortality [ 29 ] while other studies show neutral effects [ 30 ] or increased rates of infections [ 16 ]. The latter may raise safety concerns of these commonly prescribed group of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we could not provide evidence for a protective effect of beta-blockers on post stroke infections and mortality. Data in humans remain inconclusive with studies showing protective effects on pneumonia rates [ 13 , 14 ] and mortality [ 29 ] while other studies show neutral effects [ 30 ] or increased rates of infections [ 16 ]. The latter may raise safety concerns of these commonly prescribed group of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…From the specialists surveyed, seven cited either arterial hypertension or blood pressure on stroke admission as a risk factor for HT. Extremes values of blood pressure at admission may be a consequence of a severe neurological presentation 30 , meaning an adrenergic reaction, regardless of age and other underlying medical conditions. A recently published study 31 did not show differences in the risk of o HT or clinical outcomes of patients treated to lower blood pressure targets (Systolic Blood Pressure<140 mmHg) and standard therapy (Systolic Blood Pressure<180 mmHg) after treatment with intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators found no effect on outcomes (stroke severity, recurrent stroke, or mortality) with the use of BB for pre-stroke hypertension therapy. Phelan and colleagues found a decrease in the in-hospital mortality in patients with AIS who had their home BB therapy continued during the first 3 days of AIS versus patients in whom BB therapy was discontinued [35]. This was despite a higher comorbid profile among patients on BB therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Phelan and colleagues found a decrease in the in-hospital mortality in patients with AIS who had their home BB therapy continued during the first 3 days of AIS versus patients in whom BB therapy was discontinued [35]. This was despite a higher comorbid profile among patients on BB therapy [35]. Similarly, Tziomalos found worse in-hospital outcomes in patients treated with BB prior to AIS, than in those not treated with BB [36].…”
Section: Discussionmentioning
confidence: 99%